Test Data Compression with Alternating Equal-Run-Length Coding - S, Sivanantham; Babu S, Aravind; Ramki, Babu; P.S, Mallick (International Journal of Engineering and Technology, 2018)
This paper presents a new X-filling algorithm for test power reduction and a novel encoding technique for test data compression in scan-based VLSI testing. The proposed encoding technique focuses on replacing redundant runs of the equal-run-length vector with a shorter codeword. The effectiveness of this compression method depends on a number of repeated runs occur in the fully specified test set. In order to maximize the repeated runs with equal run length, the unspecified bits in the test cubes are filled with the proposed technique called alternating equal-run-length (AERL) filling. The resultant test data are compressed using the proposed alternating equal-run-length coding to reduce the test data volume. Efficient decompression architecture is also presented to decode the original data with lesser area overhead and power. Experimental results obtained from larger ISCAS'89 benchmark circuits show the efficiency of the proposed work. The AERL achieves up to 82.05 % of compression ratio as well as up to 39.81% and 93.20 % of peak and average-power transitions in scan-in mode during IC testing.Â Â